A fable for Tubino - DOI: 10.4025/reveducfis.v20i1.6923 - Krebs, Ruy Jornada (2009)
The objective of this essay is to pay a tribute to manoel José Gomes Tubino, died in 18 of December of 2008. The text is composed by two parts. In the first one the Tubino’s role in the creation of graduate programs in Physical Education in Brazil is commented, and in the second one it is emphasized the Tubino’s concern with the infallible and moralizing aspect of the fables used in school textbooks.